CHINA-VIETNAM: THE DISPUTE OVER THE PARACELS AND SPRATLYS (Proceedings of International Educators Conference, 2024)
This paper analyses the developments in Vietnam’s relations with China from the time both countries normalised relations in November 1991 to the present. It demonstrates that not withstanding the historical baggage and the asymmetry of power of the two countries, relations have been improving incrementally over the last seven years. However, four issues affecting their relationship – all of which pertain to their shared land and sea borders – remain outstanding. There seems to be the political will on the part of both governments to resolve two of the four issues by the year 2000. They are the demarcation of the land border and the Tonkin (Bac To) Gulf. The remaining two issues – the Paracels and the Spratlys – are unlikely to be resolved any time soon. The paper concludes that relations in the short and medium term will continue to develop on an even keel.